Identification of Brucella genus and eight Brucella species by Luminex bead-based suspension array. (April 2018) - Lusk Pfefer, Tina S.; Timme, Ruth; Kase, Julie A.
Abstract: Globally, unpasteurized milk products are vehicles for the transmission of brucellosis, a zoonosis responsible for cases of foodborne illness in the United States and elsewhere. Existing PCR assays to detect Brucella species are restricted by the resolution of band sizes on a gel or the number of fluorescent channels in a single real-time system. The Luminex bead-based suspension array is performed in a 96-well plate allowing for high throughput screening of up to 100 targets in one sample with easily discernible results. We have developed an array using the Bio-Plex 200 to differentiate the most common Brucella species: B. abortus, B. melitensis, B. suis, B. suis bv5, B. canis, B. ovis, B. pinnipedia, and B. neotomae, as well as Brucella genus. All probes showed high specificity, with no cross-reaction with non- Brucella strains. We could detect pure DNA from B. abortus, B. melitensis, and genus-level Brucella at concentrations of ≤5 fg/μL. Pure DNA from all other species tested positive at concentrations well below 500 fg/μL and we positively identified B. neotomae in six artificially contaminated cheese and milk products. An intra-laboratory verification further demonstrated the assay's accuracy and robustness in the rapid screening (3–4 h including PCR) of DNA. Highlights: A PCR-based Luminex assay to speciate Brucella is presented. The assay targets eight Brucella species and genus-level Brucella. B. neotomae was detected in inoculated cheese and milk using the assay. This accurate, high-throughput assay array is completed in 3–4 h. Bacterial isolates or DNA-extracted food samples can be screened with this assay.